REFLECTIONS ON LEARNING AND MEMORY IN LIGHT OF THE EXECUTIVE FUNCTION OF MEMORY - Tomé, José Manuel Salum (Seven Editora, 2026)
Animals in the natural environment face multiple challenges in order to survive. One of the most fundamental is obtaining food, and for this task to be effective they must remember the places they have previously explored. Successfully solving this task requires a system of memory and attention. “Attention is understood as the mechanism that activates the processes involved in the processing of information, participates in and facilitates the functioning of all cognitive processes, regulating and exerting control over them.” (García, 1997; Rosello, 1998; Ruiz-Vargas, 1987). Attention is a selective process of receiving information that controls the threshold of our cognitive system and also performs alert functions, being involved in educational learning and study processes, participating as an alert mechanism in high-risk professions, in the concentration and focus of research, and in memory and learning, among others.